PENGARUH KEBUDAYAAN, DORONGAN EKONOMI DAN TINGKAT PENDIDIKAN TERHADAP PRAKTEK MENAIKKAN HARGA JUAL BELI PADA OBJEK WISATA DANAU TOBA SUMATERA UTARA - Sitohang, Susan Rumanti; Sinaga, Dearlina; Surya, Aldwin (LPPM Universitas Darma Agung, 2020)
The practice of increasing selling prices can be influenced by many factors, particularly habitual factors and factors inherent in the individual business actor himself. These factors are cultural factors, economic encouragement and education. This study aims at finding the influence of culture, economic encouragement and the level of education partially and simultaneously influencing the practice of increasing the buying and selling price of the Lake Toba Tourism Object, North Sumatra. The population of this research is 57 restaurant entrepreneurs. In determining the number of samples, saturated samples used so that the sample is 57 businesses. The data collection techniques used in this study are questionnaires, interviews and documentation studies. While the data analysis techniques used are the classical assumption test, multiple regression, partial t test, simultaneous F test and the coefficient of determination. The results show that cultural variables have a significant effect on the selling and buying prices of restaurant businesses at Lake Toba attractions. When the culture of community is better, the selling price is also better. Economic drive variables have a significant effect on the selling and buying prices of restaurant businesses at Lake Toba attractions. The better the economic boost, the better the selling price. The level of education variable has a significant effect on the selling price of restaurant products at Lake Toba attractions because the better the level of education, the better the selling price. Cultural variables, economic drive, and education level simultaneously have a significant effect on a significant effect on the selling price of restaurant products at Lake Toba tourism objects. As much as 86.90% of the variation in selling prices can be explained by culture, economic drive and education level simultaneously, while the remaining 13.10% is explained by other factors, such as variables such as variables such as location and type of business